Underactive Bladder - Chapple, Christopher R.; Wein, Alan J.; Osman, Nadir I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
In this book, the authors look at the field of underactive bladder and its presentation, clinical diagnosis, potential etiopathogenesis and treatment. While the editors address a great deal of background information, they clearly identify that many limitations still exist to clinical diagnosis and urodynamic evaluation, and in particular a dearth of appropriate treatment options. This complex condition needs to be recognized and identified in the routine evaluation and clinical management of patients.
1. Pathophysiology and Associations -- 2. Non-invasive diagnostics for Detrusor underactivity/Underactive bladder -- 3. Invasive Diagnostic Tests -- 4. Epidemiology of Underactive Bladder -- 5. Indications For Treatment -- 6. Pharmacologic Treatment of Underactive Bladder -- 7. Surgical Treatment : Outlet Reduction , Men and Women -- 8. Neurostimulation and Neuromodulation for the Treatment for the Underactive Bladder -- 9. Reduction Cystoplasty -- 10. Bladder Wrap Procedures -- 11. Tissue Engineering and cell therapy for underactive bladder: current and future approaches -- 12. Reflections and the Way Forward.
Keywords: Medicine; Rectum -- Surgery; Urology; Medicine & Public Health; Urology; Colorectal Surgery